Конкурентоспроможність вищої освіти України у вимірі міжнародних систем ранжування - Левченко, О. М.; Царенко, І. О.; Levchenko, O.; Tsarenko, I. (ДонНУ, 2016)
Предметом дослідження є стан системи вищої освіти України в рамках компаративного аналізу міжнародних систем ранжування. Мета статті – здійснити аналіз рівня конкурентоспроможності національної системи вищої освіти та виокремити проблемні аспекти її розвитку. В статті використані описовий метод – для розкриття наявної інформації по кожній системі ранжування, метод узагальнень і графічний метод – для демонстрації складових загальної рейтингової оцінки та її динаміки у розрізі країн. Результатом роботи є проведений аналіз стану вищої освіти України з огляду на необхідність посилення її конкурентоспроможності на основі таких світових рейтингів як: Universitas21 або U21 та QS Higher Education System Strength. Сфера застосування результатів дослідження – національна програма розвитку системи вищої освіти України. В статті наведено складові SWOT-аналізу, особливості методологій міжнародних систем ранжування вищої освіти на макрорівні. Розглянуті аналітичні звіти проведеного дослідження конкурентоспроможності систем вищої освіти з використаннях вищезазначених рейтингів. Оцінені позиції вищої освіти України в межах світових систем ранжування. Побудовано матрицю SWOT-аналізу вищої освіти України. Запропоновано напрями стратегічного управління щодо посилення конкурентоспроможності вищої освіти України на ринку освітніх послуг. The subject of research is the state of higher education of Ukraine within the comparative analysis of international rankings. The purpose of the paper - to analyse the level of competitiveness the national higher education system and identify the problematic aspects of its development. The paper is used the descriptive method - for disclosing the information available for each system of ranking, method of summarizing and graphical method - to show the components of the overall rating assessment and its dynamics by countries. The result of this research is the conducted analysis of the state of higher education of Ukraine because of the need to strengthen its competitiveness on the basis of such international rankings as: Universitas21 or U21 and QS Higher Education System Strength. The sphere of application of the research results is the national program for development of higher education of Ukraine. The components of SWOT-analysis, the peculiarities of methodologies of the international rankings of higher education on the macro-level are shown in this paper. The analytical reports of the conducted research of competitiveness of higher education with using the aforementioned ratings are considered. The positions of the system of higher education of Ukraine within the framework of international rankings are estimated. The SWOT-analysis of higher education of Ukraine is done. The directions of strategic management to enhance the competitiveness of higher education of Ukraine on the market of educational services are proposed.
The competitiveness of higher education of Ukraine in dimension of international rankings
Keywords: SWOT-аналіз; рейтинг; ранжування; SWOT-аналіз вищої освіти; система ранжування ВНЗ; SWOT-analysis; ratings; rankings; SWOT-analysis of higher educatio; system of universities ranking; Universitas2; Universitas21; U21; QS Higher Education System Strength